Mathematical algorithms for the implementation of B-Splines - Emi Marlina Mohd Nain (Fakulti Sains dan Teknologi, 2011)
CAGD is the abbreviation for "Computer Aided Geometric Design". This is a study of mathematical representation of curves and surfaces which is suitable for computer graphics display and rendering. It has wide applications in industries such as car, aircraft and ship building. It also contributes to the advancement of the research in the area of the image analysis and pattern recognition.